Sinergitas akselerasi lembaga Badan Penyelenggara Jaminan Produk Halal Dan Lembaga Pemeriksa Halal dalam implementasi sertifikasi halal industri di Indonesia - Nurdiansyah, Muhammad Rizki Dwi (Journal of Halal Industry Studies, 2023)
This research discusses Indonesia with its majority Muslim population, which has resulted in a high demand for halal products. The aim of this study is to answer questions about the formulation of BPJPH and LPH in implementing halal certification for the industry in Indonesia. As a predominantly Muslim country, Indonesia needs to ensure the legality of halal products circulating or entering the country. This research utilizes a qualitative descriptive research method as it describes information based on facts or actual events obtained directly from the field, using literature study as the data collection technique. The research findings indicate that the procedures for determining halal certification in the industrial sector in Indonesia are carried out by the BPJPH and LPH institutions. The government, through legislation, has regulated the assurance of halal products in Indonesia. The halal quality of products can be determined by implementing halal certification, which starts from the determination of ingredients, production processes, and the final product.